THE RELATIONSHIP BETWEEN PERSONALITY AND PSYCHOLOGICAL WELL BEING TOWARD ADOLESCENTS IN DISASTER-PRONE AREAS IN PADANG CITY - Helena Patricia; Chamy Rahmatiqa; Emira Apriyeni (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2020)
Abstract Background: Indonesia, particularly Padang City, West Sumatra, is a prone-area toward natural disasters related to geographical, geological and demographic conditions. Natural disasters give a very significant impact on physical, psychological and social. The psychological impact that most often appears in disaster cases is Post Traumatic Stress Disorder (PTSD). One who is prone to experiencing PTSD is adolescents. To prevent PTSD from occurring, good psychological well-being is needed. The factors that influence psychological well-being is personality. Objectives: This study aimed to analyze the relationship of personality with psychological well-being toward adolescents in disaster-prone areas in padang city Methods: This study is an analytical study with a cross sectional approach. This research was conducted in three disaster-prone districts in Padang City, namely North Padang, South Padang, and Koto Tangah. Data were collected through distributing questionnaires to 156 adolescents who were selected by purposive sampling. Data were collected by questionnaire and analyzed descriptively using univariate analysis,and bivariate analysis with chi square test. Results: The results of this study found that 85 respondents (54.5%) had low psychological well-being, and 108 respondents (69.2%) had introverted personality types. The results of the bivariate analysis found a relationship between personality toward psychological well-being with 0.010 P value. Conclusion: The results found that there was a relationship between personality toward psychological well-being adolescents in disaster-prone areas in Padang City. It is recommended for adolescents, parents and teachers to pay attention about the personality and support the students so that adolescents have high psychological well-being. Keywords:Psychological well-being, personality, Adolescent, Disaster-prone area.